2009
DOI: 10.1074/jbc.m806693200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Hyperpolarization Drives Cation Influx and Fungicidal Activity of Amiodarone

Abstract: Cationic amphipathic drugs, such as amiodarone, interact preferentially with lipid membranes to exert their biological effect. In the yeast Saccharomyces cerevisiae, toxic levels of amiodarone trigger a rapid influx of Ca 2؉ that can overwhelm cellular homeostasis and lead to cell death. To better understand the mechanistic basis of antifungal activity, we assessed the effect of the drug on membrane potential. We show that low concentrations of amiodarone (0.1-2 M) elicit an immediate, dose-dependent hyperpola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 35 publications
9
79
1
Order By: Relevance
“…Quinacrine produced a remarkable increase of Ca 2+ uptake, but the absence of an effect of this compound on growth, brings some doubt about the proposal that the increased Ca 2+ is responsible for the death of yeast cells, as suggested by several authors [18][19][20][21][22][23][24][25][26]. It appears that in order to inhibit growth, other effects are involved.…”
Section: Quinacrine and Acridine Orange Dyesmentioning
confidence: 91%
See 1 more Smart Citation
“…Quinacrine produced a remarkable increase of Ca 2+ uptake, but the absence of an effect of this compound on growth, brings some doubt about the proposal that the increased Ca 2+ is responsible for the death of yeast cells, as suggested by several authors [18][19][20][21][22][23][24][25][26]. It appears that in order to inhibit growth, other effects are involved.…”
Section: Quinacrine and Acridine Orange Dyesmentioning
confidence: 91%
“…These studies were continued by Muend and Rao [20], and later by Maresova et al [21], who found a plasma membrane hyperpolarization that drives Ca 2+ influx into S.…”
Section: Introductionmentioning
confidence: 86%
“…Increased pH in of the pma1-105 mutant was really a surprising observation, not easy to explain, as its inability to grow at low pH was generally assumed to be due to an excessive cytosol acidification. However, the main trouble with this mutant might perhaps be the significantly decreased membrane potential (Maresova et al, 2009;Stevens and Nichols, 2007) and thus reduced proton-motive force necessary for nutrient uptake. When plasma membrane is depolarized, and Pma1 does not have sufficient capacity to extrude protons, the cell might try to increase the pH by transporting protons elsewhere (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a cardiac cell, the incorporation of amiodarone into the cell membrane perturbs the properties of the phospholipid bilayer structure and contributes to its antiarrhythmic abilities. 35 Table 1: For the individual cells defined in the ion image in Figure 1C, the percent area of coverage, average amiodarone counts per pixel summed across the depth scale and cell diameters were calculated. The average amiodarone count per pixel was calculated by dividing the backgroundsubtracted intensity of the peak at m/z 646.0 summed over the ROI by the total number of pixels in the selected ROI.…”
Section: Experimental Methodsmentioning
confidence: 99%